Police Image Restoration: A Case Study of the Stampede (Crowd Crisis) at Kanjuruhan Malang - Purnama Ayu Rizky; Jesslyn Velingsia (Politicos: Jurnal Politik Dan Pemerintahan, 2024)
On October 1 2022, 131 people died in a "riot" at the Kanjuruhan Stadium, Malang, East Java. The riot occurred after Persebaya silenced Arema, the host football group. Arema supporters, who did not accept the defeat, then rushed into the stadium, so that the police (Polri) who were on guard at the location, dispersed the crowd by spraying tear gas, leaving the exit doors tightly closed, thus triggering massive panic. What happened in Kanjuruhan was an example of a stampede or crowd crisis which created chaotic conditions to the point that many were found dead. The aftermath of the tragedy was the erosion of public trust in the National Police institution. This research outlines the image restoration strategy of the National Police in overcoming the Kanjuruhan stampede, using Bennoit's Image Restoration theory. This qualitative research uses descriptive analysis to explain this phenomenon. The research results show that strategies to improve the image of the National Police, including denial, evading responsibility, reducing effectiveness, corrective action, mortification, have in fact proven to be ineffective. Because, this strategy failed to boost the institution's positive image. Thus, public trust in this institution has collapsed to this day.